How Leisure Involvement Affects Repurchase Intention in Fitness Clubs? The Mediating Role of Commercial Friendship - Wang, Yanting; Gao, Yi; Wang, Fong-Jia (Frontiers in Sports and Active Living, 2022)
This study explores the relationships among leisure involvement, business or commercial friendship, satisfaction, and willingness to repurchase in customers’ use of customized fitness services. This study randomly sampled and analyzed the customers of fitness clubs (N = 234) in China. The results showed that leisure involvement had a positive impact on repurchase intention and satisfaction. Moreover, the mediating effect of commercial friendship was found in the relationship between leisure involvement, repurchase intention, and satisfaction. Overall, the study contributes to the literature by exploring the interaction effects of different types of consumer leisure involvement and commercial friendships in customized fitness services models on satisfaction and repurchase intentions’.